2022
DOI: 10.1021/acsami.1c19297
|View full text |Cite
|
Sign up to set email alerts
|

Giant Functional Properties in Porous Electroceramics through Additive Manufacturing of Capillary Suspensions

Abstract: Dedicated hierarchical structuring of functional ceramics can be used to shift the limits of functionality. This work presents the manufacturing of highly open porous, hierarchically structured barium titanate ceramics with 3-3 connectivity via direct ink writing of capillary suspension-type inks. The pore size of the printed struts (∼1 μm) is combined with a printed mesostructure (∼100 μm). The self-organized particle network, driven by strong capillary forces in the ternary solid/fluid/fluid ink, results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
1
6
0
Order By: Relevance
“…In this study, nonetheless, Pluronic F-127 was found to have noticeably affected the particle-stabilized emulsion. In addition, the microstructure of EF appeared very similar to that of sintered ceramic capillary suspensions reported in the literature, ,, although the two material systems are of different natures. As propyl gallate was adsorbed on the particles endowing them with an overall weak hydrophobicity, the hydrophobic interactions between the alumina particles and the PPO cores of Pluronic F-127 micelles could interfere with the particle adsorption to the oil–water interface and lead to particle agglomeration.…”
Section: Results and Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In this study, nonetheless, Pluronic F-127 was found to have noticeably affected the particle-stabilized emulsion. In addition, the microstructure of EF appeared very similar to that of sintered ceramic capillary suspensions reported in the literature, ,, although the two material systems are of different natures. As propyl gallate was adsorbed on the particles endowing them with an overall weak hydrophobicity, the hydrophobic interactions between the alumina particles and the PPO cores of Pluronic F-127 micelles could interfere with the particle adsorption to the oil–water interface and lead to particle agglomeration.…”
Section: Results and Discussionsupporting
confidence: 74%
“…Direct ink writing (DIW), also known as robocasting, is an extrusion-based 3D printing technique that allows for easy and accurate control of the printed structure as per the computer-aided design. , Fundamental to this technique is the formulation of viscoelastic inks. In DIW, the ink must exhibit a shear-thinning behavior to facilitate extrusion and a sufficiently high storage modulus as well as yield stress for good shape retention and structural integrity. , Recently, hierarchical porous ceramics have been fabricated by DIW in combination with colloidal processing techniques, such as the use of sacrificial templates, , capillary suspensions, ,, as well as foam , and emulsion ,, templating, to incorporate additional levels of microporosity that are typically beyond the resolution of DIW. Among them, DIW of foams and emulsions is a facile and effective approach to prepare mechanically efficient hierarchical porous ceramics with fine control capability over the microporous structure …”
Section: Introductionmentioning
confidence: 99%
“…Additive manufacturing technology has the advantages of fast molding, high precision, wide material applicability, and direct forming, which can realize the rapid fabrication of devices with complex structures [10]. At present, additive manufacturing technology has been widely applied in the fabrication of ultrasonic phased arrays [11], such as direct ink writing [12,13], digital light processing [14,15], and stereolithography [16,17]. Although these methods solve the shortcomings of traditional manufacturing processes, this onestep process of modeling ceramic bodies makes it no longer applicable to prepare electrodes by magnetron sputtering.…”
Section: Introductionmentioning
confidence: 99%
“…The rising three-dimensional (3D) printing technique, with its unparalleled freedom to create complex, customized geometries with low cost, shows great promise in controlling the internal morphologies and architectures of cellular materials. Especially, 3D printing of silicones could be realized using direct ink writing (DIW), ,,, inkjet printing, , embedded 3D printing, , vat polymerization, , and expanded techniques for higher resolution. , Mechanical responses of the printed foams could be well predicted, designed, and/or optimized by digital techniques such as simulation and machine learning , and further tailored by controlling the inner structure (such as the polymer network , and filler orientation , ) of the printed filaments. In addition, by introducing micro- or nanoscale pores in the 3D printed filaments using a sacrificial templating concept, a hierarchical porous structure could be achieved, endowing the foam with ultraelasticity (i.e., extreme compressibility and cyclic endurance) and much enhanced active surface area compared to its nonhierarchical counterparts, , which is favorable for high-tech fields such as aerospace, energy, and bioengineering.…”
Section: Introductionmentioning
confidence: 99%